Tuning thermoelectricity in a Bi2Se3 topological insulator via varied film thickness. (12th January 2016) - Guo, Minghua; Wang, Zhenyu; Xu, Yong; Huang, Huaqing; Zang, Yunyi; Liu, Chang; Duan, Wenhui; Gan, Zhongxue; Zhang, Shou-Cheng; He, Ke; Ma, Xucun; Xue, Qikun; et al.
Abstract: We report thermoelectric transport studies on Bi2 Se3 topological insulator thin films with varied thickness grown by molecular beam epitaxy. We find that the Seebeck coefficient and thermoelectric power factor decrease systematically with the reduction of film thickness. These experimental observations can be explained quantitatively by theoretical calculations based on realistic electronic band structure of the Bi2 Se3 thin films. This work illustrates the crucial role played by the topological surface states on the thermoelectric transport of topological insulators, and sheds new light on further improvement of their thermoelectric performance.